Case Report: Third-degree atrioventricular block and respiratory failure caused by clozapine poisoning - Tian, Qiaoxin; Shang, Ruikai; Liu, Yuru; Liu, Hongyu; Zheng, Yingying; Jian, Xiangdong (Frontiers in Pharmacology, 2025)
BackgroundThis case report details the management of a patient who presented with third-degree atrioventricular block and rhabdomyolysis secondary to clozapine intoxication.Case summaryThe patient was a 55-year-old man who took 100 tablets of clozapine and was transferred to our hospital from a lower-level hospital for treatment. Upon arrival at our hospital, he was in a coma and was assisted with mechanical ventilation. Upon admission, based on the results of toxicological tests and laboratory examination; computed tomography, magnetic resonance imaging, and echocardiography findings, and the patient’s clinical manifestations, the diagnosis of third-degree atrioventricular block and rhabdomyolysis due to excessive intake of clozapine was confirmed. The patient received comprehensive treatment, including blood purification, organ protection, nutritional support, and cardiac rate enhancement. The patient was clinically cured and discharged. Clozapine-induced central nervous system inhibition can be dose-dependent, thus leading to coma and organ damage at high doses. Considering that no specific antidotes are available, cases involving clozapine toxicity require careful management. In this instance, beyond the central nervous system and respiratory depression, the patient also exhibited third-degree atrioventricular block and rhabdomyolysis, which warrant significant attention.ConclusionMany patients with clozapine poisoning have been admitted to our department. Clozapine poisoning mostly causes symptoms such as accelerated heart rate, but in our patient’s case, third-degree atrioventricular block and rhabdomyolysis symptoms occurred unusually. For clozapine poisoning, timely and appropriate management is crucial for the recovery of patients.